Demographic Recovery of a Reef Fish Population Over 30 Years of Spawning Aggregation Site Protection - Rosemond, R. Claire; Nemeth, Richard S.; Heppell, Scott A. (Frontiers in Marine Science, 2022)
Over 200 species of reef fish around the world form spawning aggregations to reproduce at specific times and locations. The locations of many reef fish spawning aggregations in the Caribbean have been known and fished for decades. Red Hind (Epinephelus guttatus), a species of grouper important in Caribbean fisheries, migrate to form spawning aggregations which have historically experienced intense fishing pressure. The Red Hind Bank Marine Conservation District (MCD) was established in the United States Virgin Islands to protect a known Red Hind spawning aggregation site. The MCD was closed seasonally to fishing in 1990 and then permanently in 1999. Our goal was to evaluate the success of this marine conservation effort by assessing how the Red Hind population at the spawning aggregation responded to changing levels of protection. We documented Red Hind population demographics at the spawning aggregation site in the MCD during peak spawning events from 2018 to 2020. After 30 years of protection, the mean size of Red Hind at the spawning aggregation increased by >35% and the population sex ratio of females to males was less skewed compared to population characteristics at the spawning aggregation prior to protection. To evaluate stock status relative to management benchmarks, we used length-based stock assessment models that included in situ size distribution data spanning 1988 to 2020 to estimate population spawning potential ratio (SPR) over time. We found that the SPR of the Red Hind population at the spawning aggregation prior to protection was 0.32 (95% CI: 0.25, 0.39) and under seasonal protection, The SPR increased slightly to 0.35 (95% CI: 0.28, 0.42). Under permanent protection, The SPR increased to its highest value yet at 0.49 (95% CI: 0.42, 0.56), which is above the benchmark value considered sustainable for many fish species. Our work demonstrates demographic recovery of the protected Red Hind spawning population and highlights the value of using size distribution data to evaluate the response of data-limited reef fish populations to seasonal and permanent protection at spawning aggregation sites.